Evaluation of the Anticancer, Anti-Inflammatory, and Antioxidant Properties of Various Extracts of Annona Squamosa L. - Nour Awada; Abeer Ayoub; Ali Jaber; Farah Ibrahim; Nadine El Ghotmi; Edmond Cheble (Tabriz University of Medical Sciences, 2023)
Background: Screening medicinal plants for their biological activities and phytochemicals is important for finding safe and potent new compounds for therapeutic use. The current investigation was conducted in extracts of Lebanese A. squamosa (leaves and bark) to evaluate the antioxidant, anticancer, and anti-inflammatory activities. Methods: Seven extracts were prepared by ultrasound-assisted extraction (UAE) or microwave-assisted extraction (MAE), and using various solvents. The evaluation of antioxidant activity was done using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, the anticancer activity assessed on the colon cancer HCT116 cell line was determined by water-soluble tetrazolium-1 (WST-1) viability assay. Finally, the anti-inflammatory activity was investigated by measuring the secreted amounts of prostaglandin E2 (PGE2) and interleukin 6 (IL-6) using. Results: The total phenolic contents were in the range between 27.3 to 179.5 mg GAE/g of plant extract, while total flavonoid contents were between 8.3 to 150.8 mg RE/g of plant extract. DPPH assay showed high antioxidant activity for the methanolic extracts obtained by UAE in both natural dried leaves and bark with IC50 values of 9.3 and 12.6 μg.mL-1, respectively. For WST-1 assay, methanolic extracts obtained by UAE showed a potent anti-proliferative effect against the HCT116 cell line with IC50 values ranged from 0.18 to 0.88 μg.mL-1. Also, the western blot assay suggested that these extracts may inhibit the proliferation of the HCT 116 cell line by causing cell cycle arrest through activation of the p21 pathway. Significant anti-inflammatory activity was observed due to the decrease in the secretion of IL-6 in lipopolysaccharide (LPS)-stimulated THP-1 cells. Conclusion: Therefore, the present study revealed that the dried leaves and bark of Lebanese A. squamosa methanolic extracts obtained by UAE possess effective bioactivities, and thus hold the potential application in the pharmacological field.